Influence of SCARB1 gene SNPs on serum lipid levels and susceptibility to coronary heart disease and cerebral infarction in a Chinese population - Zeng, Ting-Ting; Tang, Di-Jiao; Ye, Yuan-Xin; Su, Jun; Jiang, Hong (Gene, 2017)
The SCARB1 gene encodes human scavenger receptor class B type I (SR-BI), the primary receptor for high-density lipoprotein (HDL)- cholesteryl ester uptake, and polymorphisms in this gene may influence SR-BI protein expression and serum lipid levels, modulating susceptibility to coronary heart disease (CHD) and cerebral infarction (CI). Therefore, we investigated the association between singlenucleotide polymorphisms (SNPs) in the SCARB1 gene and serum lipid levels as well as risk of CHD and CI in the Chinese Han population. Genotypes in 295 CHD patients, 302 CI patients and 312 healthy controls matched for age and gender were determined by high-resolution melting (HRM). Among the 5 SNPs investigated in this study, rs10846744 and rs2278986 were significantly associated with CHD risk. The frequency of the C allele for rs10846744 and that of the T allele for rs2278986 appeared to be significantly increased in the CHD group (OR: 1.416, 95%CI: 1.128–1.778, P=0.0058 and OR: 1.681, 95%CI: 1.327–2.130, P<0.0001, respectively). CHD patients with genotypes CC and CG for rs10846744 had a higher HDL-c level than those with genotype GG, and CHD patients with genotypes CC and CT for the rs2278986 SNP had a higher HDL-c level compared to those with the TT allele. The other 3 SNPs, rs5888, rs10744182 and rs838893, showed no significant association with serum lipid levels and CHD or CI risk in the Chinese population. The CCCTT and CCTTC haplotypes of rs5888, rs10846744, rs10744182, rs2278986 and rs838893 appear to significantly increase CHD risk, whereas the CGTTC, CCTCT and TGCTC haplotypes appear to significantly reduce risk. Overall, the CCTTC and TGTTC haplotypes acted as a significant risk for CI, with the CGCTC and CCCCT haplotypes conferring significantly reduced risk. These results suggest that SCARB1 gene polymorphisms may contribute to genetic susceptibility to CHD; in particular, the C allele of rs10846744 and the C allele of rs2278986 may serve as risk and protective factors for CHD, respectively. •The SCARB1 gene SNPs were analyzed in Chinese population with CHD and CI.•The association between SNPs and serum lipids levels was estimated.•Total 5 SNPs in SCARB1 gene were identified.•2 SNPs were associated with CHD in Chinese populations.•The same 2 SNPs were associated with HDL-c levels in CHD populations.